ANALISIS FAKTOR-FAKTOR YANG MENINGKATKAN DAYA SAING PRODUK UKM MAKANAN RINGAN DI KUNINGAN - Lili Karmela Fitriani (Universitas Kuningan, 2019)
AbstractSMEs products in Kuningan district very diversed and dominated by the snack food products. This study was conducted to analyze the factors that shape the competitiveness of SMEs snacks in Kuningan. The research sample of 103 respondents of food entrepreneurs. Using multiple regression analysis. The results of the study explained that the factor of innovation and human resources has a positive influence on the competitiveness of products, while the technology and product excellence has no effect on the competitiveness of SMEs snacks in Kuningan .Keywords: Competitiveness, Innovation, Human Resources, Product Excellence AbstrakProduk UKM di Kabupaten Kuningan sangat beragam dan didominasi oleh produk makanan ringan. Penelitian ini dilakukan untuk menganalisis faktor-faktor yang membentuk daya saing produk UKM makanan ringan di Kuningan. Sampel penelitian ini sebanyak 103 responden para pelaku usaha makanan ringan. Analisis menggunakan regresi berganda. Hasil penelitian menjelaskan bahwa faktor inovasi dan sumber daya manusia memiliki pengaruh positif terhadap daya saing produk, sedangkan teknologi dan keunggulan produk tidak berpengaruh pada daya saing produk UKM makanan ringan di Kecamatan Kuningan.Kata Kunci : Daya saing, Inovasi, Sumber Daya Manusia, Keunggulan Produk